Konsep Mekanisme Pasar Menurut Abu Yusuf Dan Ibnu Khaldun Dalam Kitab Al-Muqoddimah Dan Al-Kharaj - Sifa', Moh Agus; Subakir, Ahmad (JPSDa: Jurnal Perbankan Syariah Darussalam, 2025)
This article discusses the concept of market mechanisms according to Abu Yusuf and Ibn Khaldun, with an in-depth analysis of their main works, Al-Kharaj and Al-Muqaddimah. Abu Yusuf, a jurist and economic advisor during the Abbasid Dynasty, emphasized the importance of the government's role in regulating markets to prevent injustice and exploitation. Meanwhile, Ibn Khaldun, a philosopher and historian, offered a more dynamic perspective on markets, emphasizing the balance between supply and demand and the influence of economic policy on the cycles of civilization. This research uses a qualitative method with a content analysis approach to identify similarities and differences in the views of the two figures. The results of the study show that despite having different approaches, both agree that justice and economic stability are key elements in an ideal market mechanism. It is hoped that this article will contribute to a deeper understanding of classical Islamic economic thought and its relevance in the modern economic context